Could mouth rinses be an adjuvant in the treatment of SARS‐CoV‐2 patients? An appraisal with a systematic review. Issue 1 (29th October 2021) - Gandhi, Gargi; Thimmappa, Latha; Upadhya, Nagaraja; Carnelio, Sunitha
Abstract: Objective: A wide variety of mouth rinses are available to combat micro‐organisms in the oral cavity. At the present global pandemic, the need of the hour is to control the viral infection due to the novel corona virus SARS‐COV‐2, as its port of entry is through the receptors located in the oral and pharyngeal mucosa. This systematic literature review focuses on the in vivo studies [randomized control trials (RCTs)] done on the efficacy of existing mouth rinses which have been used in reducing the viral loads. Methods: The electronic database which includes PubMed‐MEDLINE, Google scholar, Scopus, Web of Science, EMBASE, ProQuest and CINAHL was searched from December 2019 to June 2021 with appropriate Medical Subject Headings (MeSH) terms and Boolean operators. Two reviewers independently reviewed the abstracts. Results: Of the 2438 retrieved titles, 905 remained after removing duplicates. Twelve articles were eligible to be included in this review of which seven were randomized with adequate sample size. Conclusions: Mouth washes containing povidone iodine and chlorhexidine decrease the viral load transiently. Large amount of in vivo studies are of paramount importance, especially RCTs, to prove the efficacy of these mouth rinses.